Perubahan Sosial Generasi Digital Dalam Interaksi Dan Etika Komunikasi Di Perguruan Tinggi - Idawati (Prosiding, 2025)
This study aims to determine how social changes in the digital era in interaction and communication ethics in higher education, this study uses a descriptive qualitative approach with field research, the data collection process is in the form of interviews with sources from academic circles, namely 1 lecturer and 2 students of the Islamic University of Riau, observation and documentation. The results of the study indicate that there is a social change in the digital era that refers to the Habitus theory of Perre Bourdien, the intense use of digital technology is able to shape changes in social behavior, this is because of the ability to multitask, making someone familiar with digital media platforms, the way individuals process each information into an integral part of human identity. The form of social change in the digital era is in the form of social changes in the content of messages that do not consider quality but tend to consider quantity, as well as the erosion of cultural values of togetherness, and mutual cooperation, Changes in Interaction and Communication Ethics in Higher Education Changes in communication ethics in higher education, focusing on changes in the style of delivering message content that does not adhere to normative ethics, and message content that does not adhere to the ethics of honesty of messages. Changes in communication ethics refer to the accuracy of message content that violates communication ethics such as conveying messages using harsh words, the existence of neglected rights, injustice, disrespect, loss of mutual respect, and compassion.